ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY - Pingkan Amelia Anjar Ariningsih; Rananda Septanta (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to empirically test and prove the Analysis of Factors Influencing Audit Delay. The population of this study consists of companies listed on the Indonesia Stock Exchange for the period 2019 to 2024, consisting of 30 companies. The sample was taken using a purposive sampling technique, resulting in a sample of 12 companies with observations for 6 (six) years, resulting in a total of 72 audited financial reports and annual reports. The data analysis method uses panel data analysis and hypothesis testing with a significance level of 5%. The test tool used is the E-Views 12 program. Based on the results of the hypothesis testing, it is shown that Financial Distress, Audit Tenure, and the Audit Committee simultaneously have a significant influence on Audit Delay. Partially, Audit Tenure has a significant influence on Audit Delay, while Financial Distress and the Audit Committee do not have a significant influence on Audit Delay.